PENGEMBANGAN MEDIA PEMBELAJARAN SEGIEMPAT BERBASIS ADOBE FLASH DENGAN PENDEKATAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS - Adom Iman Kurnia; Sumarni; Nuranita Adiastuty (Program Studi Pendidikan Matematika Universitas Kuningan, 2025)
This study examines a persistent challenge in mathematics education: students' lack of fundamental skills in representing two-dimensional shapes within real-life contexts, an issue linked to a reliance on conventional teaching approaches. To address this, the study aimed to develop Adobe Flash-based interactive learning media for the topic of quadrilaterals and to evaluate the media's validity, practicality, and effectiveness in enhancing students' mathematical representation skills. Guided by the Plomp development framework, the research was conducted in three interconnected stages: an initial diagnostic phase focused on problem identification, a design and prototyping phase, and a final evaluation phase. Thirty students from class VII-D at SMP Negeri 1 Kuningan participated in the study during the second semester of the 2018/2019 academic year, having been selected via purposive sampling. Data were collected using various instruments, including validation sheets to assess the media and content, pre-test and post-test instruments, and questionnaires to gauge student feedback. The results indicate that the developed learning media met the criteria for validity and practicality; this conclusion is based on assessments by subject matter and media experts, as well as student feedback, which showed a positive response with an average rating of 95.72%. Furthermore, N-gain calculations revealed a measurable improvement in students' mathematical representation skills, with an average score of 0.69, indicating an improvement within the moderate category.